Reliability and validatidity of Hospital Anxiety and Depression Scale (HADS) on breast cancer survivors: Malaysia case study - Yong, Heng Weay; Hashim, Zailina; Jamil @ Osman, Zubaidah (Environmental and Occupational Health Society, 2016)
Objective: Cancer survivors may experience psychiatric or psychological disturbances during or after medical treatment, but most of it was under-reported or unrecognized by the health care professionals. Hospital Anxiety and Depression Scale (HADS) is a common and widely used tool for determining psychological distress among cancer population. This study determined the reliability and validity of both Malay and Chinese translated English version of HADS. Method: Malay and Chinese versions of HADS were administered to 150 breast cancer survivors Cronbach’s alpha coefficient and convergent validity was assessed to determine the internal consistency and the validity of the questionnaire. Result: The prevalence of anxiety was 7.3% whereas the prevalence of depression was 4.7%. The internal consistency for the full scale on Malay version was 0.87, for the anxiety subscale was 0.81 and for depression subscale was 0.73. For the scales on Chinese version, the Cronbach’s alpha (α) was 0.81, for the anxiety subscale was 0.67 and for the depression subscale was 0.70. The internal consistency of this study was found to be satisfactory with the α coefficient values of above 0.70, as the recommended values. The correlation coefficient ranged from 0.40 to 0.78 for the anxiety and depression sub- scale for both Malay and Chinese version of HADS, which showed that the correlations between the items of each subscale with its subscale were moderate. Conclusion: The Malay and Chinese version of HADS were reliable and valid instrument in assessing anxiety and depres- sion among breast cancer survivors.